2010
DOI: 10.1111/j.1755-3768.2009.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness in children with growth hormone deficiency

Abstract: Acta Ophthalmol. 2010: 88: 692–694 Abstract. Purpose:  To evaluate central corneal thickness (CCT), intraocular pressure (IOP) and eye refraction in patients with congenital growth hormone (GH) deficiency. Methods:  Retrospective case series. Forty‐five patients with growth defect treated with recombinant GH and 45 healthy children underwent ophthalmological examination, including CCT measurements, applanation tonometry and cycloplaegic refraction. Results:  The average CCT in the GH deficiency group was 570.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…Parentin et al hypothesized that this decrease took place during the first and second years of life. They claimed that rearrangements in collagen bundles and remodeling occurred in the early years of life (24) . Hussein et al studied children between the ages of 7 months and 14 years and reported that CCT was 538 µm in children under 2 years old, 546 µm in children between 2 and 4 years, 565 µm between 5 and 9 years, and 555 µm between 10 and 14 years old.…”
Section: Central Corneal Thicknessmentioning
confidence: 99%
“…Parentin et al hypothesized that this decrease took place during the first and second years of life. They claimed that rearrangements in collagen bundles and remodeling occurred in the early years of life (24) . Hussein et al studied children between the ages of 7 months and 14 years and reported that CCT was 538 µm in children under 2 years old, 546 µm in children between 2 and 4 years, 565 µm between 5 and 9 years, and 555 µm between 10 and 14 years old.…”
Section: Central Corneal Thicknessmentioning
confidence: 99%
“…4 HGH is known to act on a variety of target organs and tissues, but little is known about its possible action on the cornea. Recently several human studies have shown alterations in the thickness and biomechanics of the cornea in acromegalic patients and GH deficient children, 5-7 suggesting a role of GH in the cornea. GH exerts its effect by binding to pre-dimerized GH receptors (GHRs) located on cell plasma membranes, leading to activation of intracellular Janus-kinase 2 (JAK2).…”
Section: Introductionmentioning
confidence: 99%
“…87 Recently, human studies have shown altered thickness and biomechanics of the cornea in acromegalic patients and GH-deficient children. 8890 These findings suggest a role of GH in the cornea. We hypothesize that HGH can promote corneal wound healing and that it does so by activating phospho-STAT5 ( p-STAT5 ) signaling and promoting corneal epithelial and fibroblast proliferation and/or migration.…”
Section: Treatment Of Persistent Corneal Epithelial Defectsmentioning
confidence: 79%